ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN RENDAHNYA CAPAIAN INISIASI MENYUSUI DINI (IMD) DI DESA BANDAR SIANTAR WILAYAH KERJA PUSKESMAS BANDAR SIANTAR KABUPATEN SIMALUNGUN TAHUN 2020 - saswati saswati (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2020)
One of the Sustainable Development Goals (SDGs) is to reduce child mortality. One effort that can be done is to move the entire community in an effort to provide exclusive breastfeeding for babies for 6 (six) months but in reality based on a survey of 20 pregnant women in Bandar Siantar Village it is known that only 7 mothers who have good attitudes and 13 respondents still have lack of knowledge, attitudes and actions towards Early Breastfeeding Initiation (IMD). This research is an analytic survey research with cross sectional approach. The population in this study were all postpartum mothers in Bandar Siantar Village with a total of 36 mothers determined based on inclusion and exclusion criteria. The results showed that there was a relationship between Mother Knowledge (p-value = 0.013), Mother's Attitude (p-value = 0.003), midwife actions (p-value = 0.045) and husband's support (p-value = 0.007) with the implementation of Early Breastfeeding Initiation. Mother's Attitude (Exp (B) = 8,894) is the dominant variable related to the implementation of Early Breastfeeding Initiation in Bandar Siantar Village. It is recommended to the Badrul Aini Mother and Child Hospital to make policies, and sanctions in the form of a warning letter to health workers who do not carry out IMD in accordance with procedures. Carry out monitoring and evaluation activities and appoint the person responsible for monitoring the implementation of Early Breastfeeding Initiation. Health workers / midwives must be better able to encourage their husbands and support their mothers to immediately implement Early Breastfeeding Initiation correctly.